2018
DOI: 10.3390/ijms19010266
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid and Metformin Inhibit Invasive Phenotype Induced by TGF-β1 in C-4I and HTB-35/SiHa Human Cervical Squamous Carcinoma Cells by Acting on Different Molecular Targets

Abstract: During the progression of epithelial cancer, the cells may lose epithelial markers and gain mesenchymal phenotype via Epithelial-Mesenchymal Transition (EMT). Such transformation of epithelial cancer cells to mesenchymal-like characteristic benefits plasticity and supports their ability to migrate. The aim of this study was to evaluate the influence of natural compound Caffeic Acid (CA) alone and in combination with antidiabetic drug Metformin (Met) on metastatic progression of two human cervical squamous cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Namely, it is well recognized that both caffeic and gallic acid, that are present in EA extract, possess strong anti-proliferative and cytotoxic properties in wide range of tumor types such as those used in this study (breast, cervical, ovarian, prostate carcinoma). [51][52][53] These phenolic acids affected main signaling pathways involved in cell cycle progression and cell death. Moreover, they interfered with migrative and invasive properties, epithelial/ mesenchimal transition and even angiogenesis.…”
Section: Enzyme Inhibitory Effects Of the A Vulgaris Extractsmentioning
confidence: 99%
“…Namely, it is well recognized that both caffeic and gallic acid, that are present in EA extract, possess strong anti-proliferative and cytotoxic properties in wide range of tumor types such as those used in this study (breast, cervical, ovarian, prostate carcinoma). [51][52][53] These phenolic acids affected main signaling pathways involved in cell cycle progression and cell death. Moreover, they interfered with migrative and invasive properties, epithelial/ mesenchimal transition and even angiogenesis.…”
Section: Enzyme Inhibitory Effects Of the A Vulgaris Extractsmentioning
confidence: 99%
“…Recently, it was reported by Laskov et al [39] that Met downregulated the expression of vimentin in endometrial cancers in vitro and in vivo in diabetic patients. The incubation of cervical cancer cell lines with Met reduced cells' ability to move, as shown using functional scratch test in C4-I and HTB-35 cells stimulated with TGF-β1 [17]. Mechanistic study revealed that Met inhibited the expression of transcription factors Snail-1, ZEB-1, and Twist-1.…”
Section: Metformin Inhibits Epithelial-to-mesenchymal Transition (Emtmentioning
confidence: 93%
“…The regulation of apoptosis pathways in HTB-35 (SiHa) cells highly reflects the specificity of cervical tumor in vivo [16]. HTB-35 cells, even unstimulated with cytokines, have mesenchymal-like characteristics, especially high vimentin expression, along with enhancement of cell scattering and ability to move [17]. Another cell line, C-4I cells (ATCC, designation CRL1594) with epithelial phenotype, was derived from primary in situ tumor [18].…”
Section: Metformin Regulates Metabolism Of Metastatic Cervical Cancermentioning
confidence: 99%
See 2 more Smart Citations